MMP-responsive in situ forming hydrogel loaded with doxorubicin-encapsulated biodegradable micelles for local chemotherapy of oral squamous cell carcinoma. Issue 54 (2nd October 2019) - Li, Wei; Tao, Cheng; Wang, Jiexin; Le, Yuan; Zhang, Jianjun
Abstract : The complex construction within the oral cavity causes incomplete surgical resection of oral squamous cell carcinoma (OSCC) that may enhance the risk of recurrence and metastasis in the treatment. Abstract : The complex construction within the oral cavity causes incomplete surgical resection of oral squamous cell carcinoma (OSCC) that may enhance the risk of recurrence and metastasis in the treatment. In situ forming injectable hydrogels with minimally invasive procedures, encapsulation stability and stimuli-responsive degradation have emerged as promising carriers for local drug delivery. In this study, doxorubicin (DOX) was first encapsulated in biodegradable poly(d, l -lactide)-poly(ethylene glycol)-poly(d, l -lactide) (PDLLA-PEG-PDLLA) micelles and then loaded into an in situ injectable hyaluronic acid (HA) hydrogel, which was cross-linked by a matrix metalloproteinase-2 (MMP-2)-responsive peptide (GCRDGPQGIWGQDRCG) through a Michael addition reaction. In vitro studies demonstrated that the HA hydrogel had a sensitive MMP-2-responsive drug release profile. Investigations including MTT, live-dead, apoptosis, and wound healing assays illustrated that DOX micelle-loaded HA hydrogels exhibited outstanding cytotoxicity against squamous carcinoma cells (SCC-15). Furthermore, by in vivo studies, we also proved that HA hydrogels degraded faster in the tumor site than in normal tissue, which led to a local sustained release of DOX-loaded micelles and tumor growth inhibition of oral squamous cell carcinoma (OSCC) without any damage to the organs. Therefore, this work provides a remarkable drug delivery platform for local chemotherapy and other applications.